DESCRIPTIVE STUDY OF PULMONARY TUBERCULOSIS DISEASE GET ALONG WELL NEIGHBORS 05 COMMUNITY PILLARS 04 LAMBANGAN VILLAGE, WONOAYU DISTRICT, SIDOARJO REGENCY - Noviyanti, Reza; Moch. Bahrudin (Global Ten Public Health and Nursing Journal, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis which usually attacks the lungs. Tuberculosis is spread by man-made droplets. According to the Ministry of Health (Kemenkes), it is estimated that there will be around 397,377 cases of tuberculosis throughout Indonesia in 2021. This number increased compared to the previous year, with 351,936 cases in 2020. The knowledge of some people who do not understand to identify early about the signs of tuberculosis disease has relatively good knowledge, but people's attitudes are still not in line because they do not care about the consequences that can be caused by tuberculosis. The provision of tuberculosis health counseling affects knowledge, attitudes and behaviors to prevent tuberculosis transmission. Health education is an effective means to increase public knowledge and awareness about tuberculosis, especially in countries with a high prevalence of tuberculosis. This study aims to descriptive pulmonary tuberculosis disease in Rukun Neighbor 05 Rukun Masyarakat 04 Desa Lambangan, Wonoayu District, Sidoarjo Regency. This research is a descriptive research. The location of the study was in Rukun Neighbor 05, Rukun Masyarakat 04, Lambangan Village, Wonoayu District, Sidoarjo Regency. The number of samples in this study was 25 people. Data collection is carried out by filling out questionnaires given to respondents. Based on the results of descriptive research, respondents have good knowledge totaling 13 respondents with a percentage (52%). While respondents have sufficient knowledge amounting to 8 respondents with a percentage (32%). And at least respondents have less knowledge, amounting to 4 respondents with a percentage (16%). Keywords: Knowledge, Disease, Hypertension